(untitled) (Bangladesh Journal of Urology, 2020)
Objective: To evaluate the results of renal function after percutaneous nephrostomy in hydronephrotic kidneys in adult population. Methods: This study was performed on 57 patients of more than 18 years of age with hydronephrosis due to PUJ obstruction and split renal function <10% at the Department of Urology, Dhaka Medical College Hospital. Patients with concomitant pathologies like stone, pyonephrosis and VUJ obstruction were excluded from the study. Their evaluation included split renal function (SRF),glomerular filtration rate (GFR),specific gravity of urine draining through nephrostomy tube,volume of urine through nephrostomy tube. Statistical analysis was performed by SPSS version 13 and the test statistics used to analyse the data were descriptive statistics and Repeated measure ANOVA. Results: Mean age of the patients was 33.4+13.0 years, mean SRF increased from 6.2% at baseline to 18.6% after 6 weeks of PCN (p < 0.001), mean GFR increased from 6.2 ml/min/1.73 sq-meter at baseline to 18.6 ml/min/1.73 sq-meter at the end of week 6,mean specific gravity of urine significantly increased from 1.009 at baseline to 1.019 after 6 weeks, volume of urine at 2nd week was 316 ml/ 24 hours and nearly 363 ml/ 24 hours after 6 weeks of PCN (p < 0.001).GFR and SRF improved in 78.95% case Conclusions: Most of the poorly functioning hydronephrotic kidneys showed functional improvement following PCN and hence not all such kidneys should be removed without subjecting them to a trial of PCN. Bangladesh Journal of Urology, Vol. 21, No. 2, July 2018 p.93-97